Advancing Psychologically Informed Practice for Patients With Persistent Musculoskeletal Pain: Promise, Pitfalls, and Solutions. Issue 5 (16th April 2018) - Keefe, Francis J; Main, Chris J; George, Steven Z
Abstract: There has been growing interest in psychologically oriented pain management over the past 3 to 4 decades, including a 2011 description of psychologically informed practice (PIP) for low back pain. PIP requires a broader focus than traditional biomechanical and pathology-based approaches that have been traditionally used to manage musculoskeletal pain. A major focus of PIP is addressing the behavioral aspects of pain (ie, peoples' responses to pain) by identifying individual expectations, beliefs, and feelings as prognostic factors for clinical and occupational outcomes indicating progression to chronicity. Since 2011, the interest in PIP seems to be growing, as evidenced by its use in large trials, inclusion in scientific conferences, increasing evidence base, and expansion to other musculoskeletal pain conditions. Primary care physicians and physical therapists have delivered PIP as part of a stratified care approach involving screening and targeting of treatment for people at high risk for continued pain-associated disability. Furthermore, PIP is consistent with recent national priorities emphasizing nonpharmacological pain management options. In this perspective, PIP techniques that range in complexity are described, considerations for implementation in clinical practice are offered, and future directions that will advance the understanding of PIP are outlined.